Analisa Prestasi Pembangkit Listrik Tenaga Uap (PLTU) Berbahan Bakar BatuBara Hasil Upgrading - Deni Mulyadi, Cecep; Kristyadi, Tarsisius; Putra, Alexin; Rusirawan, Dani (Infotekmesin, 2021)
Coal is a cheap fuel, so it is widely used by steam power plants (PLTU). With many PLTUs using coal, the demand for coalÂ  increases and the quality of the coal is decreasing and the price continues to rise. With this problem, it is necessary to improveÂ  coal quality, one of which is by upgrading using a gas exhaust boiler. With using rotary dryer, the coal will be upgraded from low calorie to high calorie by reducing the moisture content, which will then be applied to the tempo cycle software 5.1. After application at cycle tempo 5.1, the best efficiency increase for PLTU can be increased efficiency and decrease coal rate, which is best obtained in the third experiment which achieved 37,041% efficiency with a coal rate of 17,567 kg / s.